Role of the Discussion Method in Increasing Student Learning Motivation in Christian Education Subjects - Sigalingging, Rico Herbet; Harefa, Senida; Naibaho, Dorlan (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2023)
This study discusses the role of the discussion method in increasing student motivation in Christian Religious Education subjects. The purpose of this research is to identify how the discussion method can influence students' learning motivation and why this method is effective in the context of Christian Religious Education subjects. The research was conducted using a qualitative approach by collecting data through classroom observations, interviews with teachers and students, and analysis of documents related to the curriculum. The results of the research show that the discussion method has a significant role in increasing students' learning motivation, by encouraging active participation, exchange of ideas, and a deeper understanding of the material. Factors such as an inclusive classroom environment, teacher facilitation, and student involvement in discussions also play a role in the effectiveness of this method. Therefore, it is recommended that the discussion method be integrated more broadly into Christian Religious Education learning in order to improve the quality of learning and student motivation.